Common Fixed Point Theorems for Commutating Mappings in Fuzzy Metric Spaces - Famei Zheng; Xiuguo Lian (Abstract and Applied Analysis)
We generalize Jungck's theorem in Jungck (1976) to fuzzy metric spaces and prove common fixed point theorems for commutative mappings in fuzzy metric spaces.